Communication across cultures. Issue 3 (8th October 2018) - Christopher, Elizabeth
Abstract: The following is a tribute to the life and work of Larry E. Smith, re‐telling some of his anecdotes, based on his experiences of the ups and downs of sharing the English language with a wide range of people in international contexts. The stories reveal, more than any words of mine could do, the extent of his contribution to cross‐cultural understanding across the world.